The reliability of morphological analyses in language samples. (January 2014) - Tommerdahl, Jodi; Kilpatrick, Cynthia D
It is currently unclear to what extent a spontaneous language sample of a given number of utterances is representative of a child's ability in morphology and syntax. This lack of information about the regularity of children's linguistic productions and the reliability of spontaneous language samples have serious implications for language testing based upon natural language. This study investigates the reliability of children's spontaneous language samples by using a test-retest procedure to examine repeated samples of various lengths (50, 100, 150, and 200 utterances) in regard to morpheme production in 23 typically developing children aged 2;6 to 3;6. Analyses indicate that out of five morphosyntactic categories studied, one of these (the contracted auxiliary) achieves an ICC for absolute agreement over .6 using 100 utterances while most others (past tense, third-person singular and the uncontracted 'be' in an auxiliary form) fail to reach a correlation above .52 even when samples of 200 utterances are compared. The study indicates that (1) 200-utterance samples did not provide a significantly greater degree of reliability than 100 utterance samples; (2) several structures that children were able to produce did not show up in a 200-utterance sample; and (3) earlier acquired morphemes were not used more reliably than more recently acquired items. The notion of reliability and its importance in the area of spontaneous language samples and language testing are also discussed.